Feeding Preference of Spodoptera exigua (Lepidoptera: Noctuidae) on Various Host Plants - A.A, Azidah; Azirun M, Sofian (Malaysian Journal of Science, 2006)
Spodoptera exigua larvae show feeding preference among the tested host plants. Host plant was the main factor for feeding preference, while larval age and time of exposure were not. However, a combination of both host plant and larval age factors also showed a significant difference in feeding preference. The hierarchy of feeding preference shown in the choice test of three host plants was reflected in the choice test of five host plants. The same sequence of cabbage, shallot and chilly was found in both choice tests. This study has shown that the S. exigua larvae prefer to feed on cabbage leaf compared to shallot, chilly, long beans and lady's finger.